Analisis Kualitas Pelayanan berdasarkan Tingkat Kepentingan, Kinerja, dan Harga Transportasi Berbasis Online di Kabupaten Mimika (Studi Kasus Transportasi Online Aplikasi Maxim) - Amelia, Isma; Paereng, Spedy (ProBisnis : Jurnal Manajemen, 2024)
Transportation service provider business people to improve the quality of service by increasing the importance, performance and price offered by online-based transportation that utilizes information technology science. This study aims to investigate the role of transportation in service quality based on the level of importance, performance and price of online-based transportation, especially in Mimika Regency by conducting a case study on the maxim application. This research method uses qualitative descriptive, Likert scale measurement. The results of this study can determine the significant level of online transportation. Online-based transportation provides quality service to consumers. Through the online-based maxim transportation application, it provides services so that it is more integrated, effective and has a positive impact on the community, traders, business actors, in addition to the above with maxim transportation opens up opportunities for new jobs for many people. With the existence of the level of importance, performance and price level of the maxim application service so as to create a positive effect that can be felt by the local government and the community directly involved. This research is expected to provide consideration to Mimika Regency and other cities in assessing transportation services for the government and the community based on the level of importance, performance and price, and this research is expected to contribute to the community in utilizing existing online-based transportation services more efficiently and effectively.